PENGARUH FAKTOR MOTIVATOR DAN FAKTOR HIGIENE TERHADAP KEPUASAN KERJA KARYAWAN HOME INDUSTRY BATIK PASIR SEMERU DI PASIRIAN - Nicky Onidis (Universitas muhammadiyah malang, 2016)
The purpose of this study firstly, to know the motivation of the motivator factors and hygiene factors at home industry batik pasir semeru in pasirian, secondly to determine employee job satisfaction, thirdly to determine the influence of motivational factors and hygiene factors on employee job satisfaction, and fourthly to determine which factors most strongly influence employee job satisfaction. Based on the results of the calculation of the average scale range of motivator factors, hygiene factors and Employee Satisfaction included the company a high category. From the calculation of the Ftest independent variables produced Ftab=4,170877 while the value of Fhit 8,467, t test motivator factors 2,587 and hygiene factors 2,877 while the value of ttab 2,04523. Results of regression analysis equation model Y=5,877+0,734X1+0,850X2+e, the next coefficient of determination (R2) value is 36,9%. It can be concluded that the motivator factors and hygiene factors variables significantly influence employee satisfaction.